Factors associated with depression in middle-aged and elderly people in Romania - Rada, Cornelia (Psichologija, 2020)
The objectives of this study were the determination of the prevalence of self-reported depressive symptoms by the Geriatric Depression Scale and the influences of variable income, physical activity, socialization and sexual activity. A total of 601 patients aged 55–93 years with a mean age of 67.32 years and a median age of 67 years participated in this study between 2016 and 2017. Non-cooperative people and individuals with strong auditory or visual sensory deficits, severe cognitive deficits, or disorders accompanied by psychotic elements with serious somatic pathology were excluded from the interviews. Employing the SPSS GENLIN procedure, an ordinal logistic model was used. Over ½ of the respondents are within the categories of moderate and severe depression, almost half of the respondents feel that their family incomes are not enough or make it hard to meet their needs, approximately 10% think they are sedentary, over ½ participate in no sexual activity, and over ¼ do not frequently respond with pleasure to partner-initiated sexual relationships. Those who were in the higher depression category perceived their income to be extremely low (p = .001), perceived themselves as sedentary (p < .001), infrequently met with friends or neighbours in their leisure time (p = .002), and had lower sexual interest (p < .001). Middle-aged adults and older adults should learn about the health benefits of physical activity, socialization and sexual activity. Social policies must take into account this low-income segment. Poverty itself can be a contributor to depressive states, and additionally, due to their low incomes, elderly people are at risk of benefiting less from pharmacotherapy and psychotherapy.
Keywords: depression; elderly; income; socialization; sexual behaviour